In vitro effects of European and Latin-American medicinal plants in CYP3A4 gene expression, glutathione levels, and P-glycoprotein activity - Mazzari, Andre Luis Dias Araujo; Lacerda, Mariella Guimarães; Milton, Flora Aparecida; Mulin Montechiari Machado, João Augusto; Sinoti, Simone Batista Pires; Toullec, Anne-Soulene; Rodrigues, Patricia Marquez; Neves, Francisco de Assis Rocha; Simeoni, Luiz Alberto; Silveira, Dâmaris; Prieto, Jose Maria (Frontiers in Pharmacology, 2022)
Many medicinal plants species from European -such as Artemisia absinthium, Equisetum arvense, Lamium album, Malva sylvestris, Morus nigra, Passiflora incarnata, Frangula purshiana, and Salix alba- as well as Latin American traditions -such as Libidibia ferrea, Bidens pilosa, Casearia sylvestris, Costus spicatus, Lippia sidoides, Monteverdia ilicifolia, Persea americana., Schinus terebinthifolia, Solidago chilensis, Syzygium cumini, Handroanthus impetiginosus, and Vernonanthura phosphorica- are shortlisted by the Brazilian National Health System for future clinical use. However, they lack many data on their action upon some key ADME targets. In this study, we assess non-toxic concentrations (up to100 μg/mL) of their infusions for in vitro ability to modulate CYP3A4 mRNA gene expression and intracellular glutathione levels in HepG2 cells, as well as P-glycoprotein (P-gp) activity in vincristine-resistant Caco-2 cells (Caco-2 VCR). We further investigated the activation of human pregnane X receptor (hPXR) in transiently co-transfected HeLa cells and the inhibition of Gamma-glutamyl transferase (GGT) in HepG2 cells. Our results demonstrate L. ferrea, C. sylvestris, M. ilicifolia, P. americana, S. terebinthifolia, S. cumini, V. phosphorica, E. arvense, P. incarnata, F. purshiana, and S. alba can significantly increase CYP3A4 mRNA gene expression in HepG2 cells. Only F. purshiana shown to do so likely via hPXR activation. P-gp activity was affected by L. ferrea, F. purshiana, S. terebinthifolia, and S. cumini. Total intracellular glutathione levels were significantly depleted by exposure to all plants except S. alba and S. cumini This was accompanied by a lower GGT activity in the case of C. spicatus, P. americana, S. alba, and S. terebinthifolia, whilst L. ferrea, P. incarnata and F. purshiana increased it. Surprisingly, S. cumini aqueous extract drastically decreased GGT activity (-48%, p<0.01). In conclusion, this preclinical study shows that the administration of some of these herbal medicines causes in vitro disturbances to key drug metabolism mechanisms. We recommend active pharmacovigilance for Libidibia ferrea (Mart.) L. P. Queiroz, Frangula purshiana Cooper, Schinus terebinthifolia Raddi, and Salix alba L. which were able to alter all targets in our preclinical study.